Prediksi persediaan air bersih dengan metode fuzzy time series cheng pada PDAM Tirta Silau Piasa - Deva Rezky Ramadhani; Fibri Rakhmawati; Rima Aprilia (Jurnal Matematika, Statistika dan Komputasi, 2024)
This research aims to determine predictions of clean water supply at PDAM Tirta Silau Piasa in 2023 using the Fuzzy Time Series Cheng method. This type of research is quantitative research using data sources, namely secondary data. This research data was taken from clean water supply data at PDAM Tirta Silau Piasa, namely data on the volume of clean water for the period January 2021 to May 2023. From the calculation results of the prediction analysis of clean water supply at PDAM Tirta Silau Piasa using the Fuzzy Time Series Cheng method, for the amount of water supply clean water in June 2023 is 443,620, with a total predicted clean water supply from 2021 to June 2023 of 12,031,703. With a MAPE value of 3%, if we look at the MAPE which is less than 10%, the results of predicting clean water supply using the Fuzzy Time Series Cheng method produce the best prediction value.